Measurement of the cross section for W-boson production in association with jets in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
We present a measurement of the cross section for W-boson production in association with jets in pp̄ collisions at s=1.96TeV. The analysis uses a data sample corresponding to an integrated luminosity of 320pb-1 collected with the CDF II detector. W bosons are identified in their electron decay channel and jets are reconstructed using a cone algorithm. For each W+≥n-jet sample (n=1-4) we measure the differential cross section dσ(pp̄→W+≥ n-jet)/dETnth-jet×B(W→eν) with respect to the transverse energy ET of the nth-highest ET jet above 20GeV, and the total cross section σ(pp̄→W+≥n-jet;ETnth-jet>25GeV)×B(W→eν), for a restricted W→eν decay phase space. The cross sections, corrected for all detector effects, can be directly compared to particle level W+jet(s) predictions. We present here comparisons to leading order and next-to-leading order predictions. © 2008 The American Physical Society.